Influence of Sodium and Potassium Levels by Thyroid Hormones Disorder in Sera of Female Patients with Cardiovascular Diseases - Alkazaz, Fatin F; Alemami, Sura A; Al taai, Mushtak Abd hinadi (Al-Nahrain Journal of Science, 2012)
Dysregulation of sodium and potassium has a characteristic role in the development of various cardiovascular disease. In the present study it sought to explore the sodium and potassium influenced by thyroid hormone disorders in sera of patients with cardiovascular disease. The study population consisted of 51 female patients with cardiovascular disease in combination with thyroid dysfunction. Thyroid function disorders were found to have hypothyroidism in 47%of patients and hyperthyroidism in 53%of patients. A significant increase in sodium and potassium concentrations were found in both patient groups. A positive significant correlation was observed between Na concentration and T4 level in sera of patients with hyperthyroidism while a significant negative correlation was found between Na concentration and TSH level in sera of patients with hypothyroidism.